Effectiveness and safety of a combination of sun protection and depigmentation agent in the treatment of epidermal hyperpigmentation - Chandrashekar, B. S.; N., Vinay (International Journal of Research in Dermatology, 2021)
Background: Medication adherence is recognized as a worldwide public health problem. As a multi-modality approach with sun protection and depigmentation is quintessential in patients with epidermal hyperpigmentation, a combination of day and night cream may be prudent for long-term improvement and compliance. Aim of the current investigation was to assess treatment outcomes and medication compliance in patients with epidermal hyperpigmentation using day and night cream in a combi-kit packaging (Melaglow day and nightTM combi-kit). Methods: Sixty patients (18-45 years) with epidermal pigmentation were enrolled in this 12-week study. Treatment effectiveness was determined by melanin index/erythema measure (dermacatch), extent, depth and density of pigmentation (fotofinder), and clinical/dermoscopic aspects (grade-1: <25%; grade-2: 25%-50%; grade-3: 50%-75%; grade-4: >75% reduction in the amount of epidermal pigment), safety, satisfaction, and compliance were assessed. Results: Out of 60 patients, 52 completed the study. The overall percentage of melanin and erythema improvement was 22.51% and 13.85%, respectively. Based on fotofinder images, 36.54% had grade-2, 34.62% had grade-3, 15.38% had grade-1, and 13.46% patients had grade-4 improvement. Based on the photographic images, 40.38% had grade-2, 32.69% had grade-3, 17.31% had a grade-1, and 9.62% had grade-4 improvement in skin color. All patients agreed that combi-kit helped in remembering and adhering to treatment. Most patients were satisfied with the treatment (84.62%), with compliance rate of 97.72%. No adverse events were reported. Conclusions: Combi-kit containing day and night cream (Melaglow day and nightTM combi-kit) was safe and effective in the treatment of epidermal pigmentation, ensuing treatment compliance, and patient satisfaction.